Entrepreneurial Education in Islamic Azad University in Order to Provide a Model - Abdulsalehi, Amir; Saffarian Hamedani, Saeed; Salehi , Mohammad (Iranian Journal of Educational Sociology, 2022)
Purpose: Considering the growing trend of education and training of entrepreneurs in the world and in our country, nurturing entrepreneurs and entering into business and creating their employment is one of the basic concerns and curiosities of the administrators in universities. Methodology: Therefore, the general purpose of the research, is the design of the model of education and training of entrepreneurs in Azad Islamic universities of Mazandaran province. The nature of the current research is exploratory and qualitative data is used in it. The statistical population of the research is experts and educational managers of Islamic Azad Universities. This group was selected to conduct the qualitative part of the research and participated in the interview process. In this field, the researcher used the snowball method to reach theoretical saturation, which reached theoretical saturation after in-depth interviews with 10 elites and experts. The data was collected using in-depth and semi-structured interviews and data analysis was done with the qualitative method of Foundation Data Theory. Findings: Based on the results, it was found that the factors affecting the education and training of entrepreneurs have three dimensions (contextual factors, causal factors and environmental factors) and consist of fifteen components. And it was shown that the consequences of education and training of entrepreneurs have 4 dimensions of improving entrepreneurial attitude, increasing well-being, continuous continuity and developing entrepreneurship with 14 components. And the strategies also have 2 dimensions, educational strategies and educational strategies. Its indicators are presented separately. Conclusion: The model of education and training of entrepreneurs to managers of Islamic Azad Universities can be used as a practical and comprehensive package in which many important details related to general concepts are seen, for all managers of Islamic Azad Universities and executive bodies in general. it is suggested.